EveryBodies issue? : Analysis of Female Body Representation and Characters in the Fortnite -video game - Hedberg, Ida (My University, 2026)
This paper aims to gather insight into Fortnite’s (an online video game) Female Characters Designs and how these Characters look and how Women are represented in the game; if this presentation contains sexist ideals. It is aimed to expose and break apart some of the design processes and causes, to the possible sexist and narrow portrayals of Women Characters in Fortnite. As a male dominated space and game, this is a different, Feminist point of view to examine Fortnite and its’ Characters. It portrays the still ongoing biases within Video Games. The study was done by looking at the gathered data, from the game itself. I asked, how are the female characters and the female body represented in the Fortnite -video game, and what possibly makes these phenomenas present, with the following specifying, how the female body is represented, how does sexism appear and do female monsters truly exist. It was found that Fortnite does express sexism in its characters design and gendered biases. The most common Female Character is thin, young and beautiful, and appeared to wear sexy or insinuating clothing (such as tight crop tops which show a significant part of abdomen, very short, tight skirts) on nearly half of the characters. Moreover, Female characters show skin nearly five times more likely than Male. Additionally, Male characters’ faces are half more likely to be covered than Female, and Female Monsters/Creatures have additional human forms, nearly every time, when Male do not. Study on Fortnite's Character Design and its possible sexism Women's Portrayal, has not been specifically explored before, to my knowledge. Thus, this paper produces further illustration of culture and practices in Games, Gaming Spaces, Digital Spaces, Character Design within a feminist frame and thus, contributes to the study of Digital Games and Cultural Studies. It declares the problematic nature of female video game characters' appearance and their lack of diversity.

Tutkimus pyrkii keräämään tietoa Fortnite –videopelin naishahmojen suunnittelusta, tarkemmin siitä, miltä nämä hahmot näyttävät ja miten he ovat edustettuina pelissä; sisältääkö se seksistisiä ihanteita tai stereotypioita. Tarkoituksena on esittää, paljastaa ja purkaa joitakin suunnitteluprosesseja ja syitä, pelin naishahmojen mahdollisiin seksistisiin ja kapeisiin kuvauksiin. Peli, peli-tilat ja ala itsessään ovat miesvaltaisia, joten feministinen näkökulma Fortniteen ja sen hahmojen tarkasteluun on uusi. Se kertoo videopeleihin vaikuttavista asenteista. Tutkimus toteutettiin keräämällä pelistä dataa, josta tarkastellaan, kuinka naishahmot ja nais-vartalo on edustettuina pelissä, ja miten ilmiöt ja piirteet mahdollisesti esitetään. Tarkemmin pohdittiin, miten nais-vartaloa kuvataan, miten seksismi ilmenee ja onko nais-hirviöitä totisesti olemassa. Tutkimus osoitti, että Fortnitessä esiintyy seksismiä, hahmojen suunnitelussa sekä sukupuolittuneissa ennakkoasenteissa. Yleisen naishahmo on laiha, nuori ja kaunis. Lähes puolella kys. hahmoista on päällä seksikkäitä tai “vihjailevia” vaatteita (kuten tiukkoja crop toppeja, jotka paljastavat merkittävän osan keskivartaloa, tai hyvin lyhyitä, tiukkoja hameita). Lisäksi naishahmoilla on ihoa näkyvillä lähes viisi kertaa todennäköisemmin kuin mieshahmoilla. Myös mieshahmojen kasvot ovat puolet useammin peitettyinä kuin naishahmojen, ja naispuolisilla hirviöillä/olennoilla on lähes aina muita muotoja (ihminen), kun taas mieshahmoilla ei. Tutkimusta, juuri Fortniten hahmomuotoilusta ja sen mahdollisesta sisäisestä seksismistä ja naisten kuvauksesta, ei ole tietääkseni aiemmen tutkittu. Näin ollen, tutkimus tuottaa uutta tietoa käytännöistä ja kulttuurista peleissä, pelitiloissa, digitaalisissa tiloissa ja hahmosuunnittelussa, feministisessä viitekehyksessä, sekä näin ollen edistää digitaalisten pelien ja kulttuurin tutkimusta. Se kertoo naispuolisten videopelihahmojen ulkonäön ongelmallisuudesta ja monimuotoisuuden puutteesta.
Keywords: Fortnite; analyysi; videopelit; (videopeli)hahmojen ulkonäkö; naishahmot; (nais)vartalojen representaatio; seksismi; feminismi; diversiteetti/monimuotoisuus